2008
DOI: 10.1243/09544062jmes683
|View full text |Cite
|
Sign up to set email alerts
|

Model reduction technique for mechanical behaviour modelling: Efficiency criteria and validity domain assessment

Abstract: The current paper presents the study of a neural network-based technique used to create fast, reduced, non-linear behavioural models. The studied approach is the use of artificial neural networks (ANNs) as a model reduction technique to create more efficient models, mostly in terms of computational speed. The test case is the deformation of a cantilever beam under large deflections (geometrical non-linearity). A reduced model is created by means of a multi-layer feed-forward neural network, a type of ANN repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The idea with the hybrid method is to first perform a response analysis for a structure using a FEM model and then subsequently to use these results to train an ANN to recognize and predict the response for future loads. As demonstrated by Ordaz-Hernandez et al [6] an ANN can be trained to predict the deformation of a nonlinear cantilevered beam. A similar approach was used by Hosseini and Abbas [7] when they predicted the deflection of clamped beams struck by a mass.…”
Section: Introductionmentioning
confidence: 99%
“…The idea with the hybrid method is to first perform a response analysis for a structure using a FEM model and then subsequently to use these results to train an ANN to recognize and predict the response for future loads. As demonstrated by Ordaz-Hernandez et al [6] an ANN can be trained to predict the deformation of a nonlinear cantilevered beam. A similar approach was used by Hosseini and Abbas [7] when they predicted the deflection of clamped beams struck by a mass.…”
Section: Introductionmentioning
confidence: 99%
“…This development aimed at a virtual reality simulator including a haptic device with force-feedback. Ordaz-Hernandez et al [38] used a multi-layer feed-forward neural network to produce a reduced model for geometrically nonlinear deformations of a cantilever beam.Ćojbašić et al [39] reported on a similar work for shell structures. Torano et al [40] used fuzzy logic, neural networks and three-dimensional (3D) finite element calculations to develop a numerical model that allows fast predictions of the response of longwall coal mining installation to changing operation conditions.…”
Section: Fem-based Training Of Neural-networkmentioning
confidence: 99%
“…Such approach consists in using the nonlinear FEM computations to provide a set of results for the training phase and can thus be classified as model reduction technique. It was applied to a number of problems such as real-time simulation of impact [16], geometrically nonlinear deformation of a cantilever beam [38] and a shell structure [8], etc. Dulong et al [12] proposed a similar approach for real-time interaction between a designer and a virtual prototype as a support to design optimization.…”
Section: Introductionmentioning
confidence: 99%